2021
DOI: 10.24127/bioedukasi.v12i2.4453
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Usia Dengan Kadar Kolesterol Masyarakat Di Kota Bandar Lampung

Abstract: Age is a factor in the emergence of various diseases caused by an unhealthy lifestyle. The purpose of this study was to see whether or not there was a relationship between age and cholesterol levels. The method used in this research is quantitative by using a cross-sectional design. This research was conducted in the 20 districts of Bandar Lampung City with a sampling technique with a stratified random sampling technique. Analysis of the data in this study, namely taking blood samples to check cholesterol leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
(6 reference statements)
0
3
0
4
Order By: Relevance
“…Based on research conducted by Saputri and Novitasari (2021), cholesterol levels will increase as the respondent ages.…”
Section: Resultsmentioning
confidence: 99%
“…Based on research conducted by Saputri and Novitasari (2021), cholesterol levels will increase as the respondent ages.…”
Section: Resultsmentioning
confidence: 99%
“…The questions presented in the questionnaire showed that the majority of respondents agreed to limit SSF consumption and believed in the impact. Health problems that can be caused in the form of hypertension, diabetes (Marine & Adiningsih, 2015), hypercholesterolmia / cholesterol levels that exceed normal levels (Saputri & Novitasari, 2021;Wiardani et al, 2011), stroke (Jayanti et al, 2017).…”
Section: Impactmentioning
confidence: 99%
“…Kadar esterogen pada perempuan menjadi penyeimbang kolesterol baik dan juga jahat, sehingga pada perempuan menopause kehilangan penyeimbang kadar. 13 jumlah kolesterol baik, kolesterol jahat dan trigliserida dalam setiap desiliter darah, normalnya <200 mg/dL. Untuk LDL normalnya <100 mg/dL, HDL normalnya <50 mg/dL dan trigliserida <150 mg/dL.…”
Section: Pembahasanunclassified